Minimum wages, wage dispersion and unemployment in search models. A~review - Alfred Garloff (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
Facing the recent German debate on the minimum wage, this paper analyses theoretical effects of minimum wages on employment and wage distribution under a frictional setting. I??review new developments in search theory and discuss the influence of the minimum wage on wages and employment under each setting. Therefore, a major theoretical focus of the paper is the integration of heterogeneity on both sides of the market in equilibrium search models. In frictional models, minimum wages are generally binding and redistribute rents from firms to workers. Employment effects are more diverse. In the homogeneous case where workers and firms are identical, minimum wages do not affect employment, while in the heterogenous case theoretical results are mixed. There is no unique connection between unemployment and minimum wages, and the effect can be negative, zero or even positive. A positive effect can arise from a reaction in labor supply. However, the most advanced models, integrating heterogeneity on both sides of the market, seem to support the hypothesis that an increase in the minimum wage generally leads to an increase in unemployment as well. In this case, a social planner faces a trade off between redistribution of rents and unemployment.
Keywords: E24; J21; J31; J64; 330; Mindestlohn - Auswirkungen; Arbeitsmarktmodell; Beschäftigungseffekte; Einkommen; Lohnstruktur; Heterogenität; Lohntheorie; Arbeitsmarkttheorie; Einkommenseffekte; Arbeitslosigkeit